2010
DOI: 10.2478/s11658-010-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib increases retinoid sensitivity in human colon cancer cell lines

Abstract: Abstract:Retinoid resistance has limited the clinical application of retinoids as differentiation-inducing and apoptosis-inducing drugs. This study was designed to investigate whether celecoxib, a selective COX-2 inhibitor, has effects on retinoid sensitivity in human colon cancer cell lines, and to determine the possible mechanism of said effects. Cell viability was measured using the MTT assay. Apoptosis was detected via Annexin-V/PI staining and the flow cytometry assay. PGE 2 production was measured with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Our study, alongside others [11], [12], has shown that combining RA with celecoxib synergistically promotes cell death of neuroblastoma cells in vitro . It is likely that inhibition of AA metabolism by cyclooxygenases and lipooxygenases promotes cell death by two mechanisms: firstly by preventing the synthesis of mediators of cell survival and, secondly, by promoting an accumulation of AA [36].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study, alongside others [11], [12], has shown that combining RA with celecoxib synergistically promotes cell death of neuroblastoma cells in vitro . It is likely that inhibition of AA metabolism by cyclooxygenases and lipooxygenases promotes cell death by two mechanisms: firstly by preventing the synthesis of mediators of cell survival and, secondly, by promoting an accumulation of AA [36].…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies suggest that PGE2 is an important mediator of RA-induced cell survival signalling [38][40]. However, later studies, including this study, have shown that exogenous PGE2 does not affect ATRA and celecoxib-induced cell death [11]. Results from a range of experimental approaches support a COX2-independent mechanism for RA mediated cell survival signalling.…”
Section: Discussionmentioning
confidence: 45%
“…Overexpression of RARβ induced growth arrest and apoptosis in HSC4 and HO-1-N-1 oral cancer cell lines that have very low RARβ expression and resistance to RA (60), and downregulation of RARβ blocked the growth-inhibitory effect of RA in HNSCC cells (61). In addition, induction of RARβ increased retinoid sensitivity and suppressed EMT in cancer cells (62)(63)(64). RARβ expression has been reported to be activated by a rapid demethylation of its gene promoter or the removal of HDAC1 from the RARβ gene (65,66).…”
Section: Ccl28 Treatment Inhibits Invasion and Emt In Oscc Cellsmentioning
confidence: 99%
“…These ligands are known to have different affinity for RA receptors. Specifically, RAR subtypes have a higher affinity to and become activated by ATRA than other RA ligands [ 10 , 11 ]. 9-cis RA binds to both RXR and RAR receptors but with higher affinity to RXR [ 10 ].…”
Section: Introductionmentioning
confidence: 99%